2005
DOI: 10.1182/blood-2005-02-0572
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells xenografted directly to rat liver are differentiated into human hepatocytes without fusion

Abstract: Hepatic transdifferentiation of bone marrow cells has been previously demonstrated by intravenous administration of donor cells, which may recirculate to the liver after undergoing proliferation and differentiation in the recipient's bone marrow. In the present study, to elucidate which cellular components of human bone marrow more potently differentiate into hepatocytes, we fractionated human bone marrow cells into mesenchymal stem cells (MSCs) Schwartz et al 1 demonstrated that multipotent adult progenitor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
347
6
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 555 publications
(377 citation statements)
references
References 50 publications
15
347
6
9
Order By: Relevance
“…A study reported that 2.5%–5% is necessary for reversing the liver injuries 59. We also observed additional CM‐Dil + /ALB + cells in the GF‐PEI‐MSN complex group; however, low amounts of these cells could not significantly reverse the injured liver, which was mentioned by previous investigators 60. One explanation for this low differentiation level may be that limited space is available for the donor cells to integrate into the CCl 4 ‐treated mouse,61 and they do so with low efficiency.…”
Section: Resultssupporting
confidence: 48%
“…A study reported that 2.5%–5% is necessary for reversing the liver injuries 59. We also observed additional CM‐Dil + /ALB + cells in the GF‐PEI‐MSN complex group; however, low amounts of these cells could not significantly reverse the injured liver, which was mentioned by previous investigators 60. One explanation for this low differentiation level may be that limited space is available for the donor cells to integrate into the CCl 4 ‐treated mouse,61 and they do so with low efficiency.…”
Section: Resultssupporting
confidence: 48%
“…Nevertheless, when human BM stem cell fractions were directly xenografted into rat liver damaged with allyl alcohol, only the fraction of MSCs developed into hepatocyte-like cells, positive for mRNA albumin expression. 42 These findings are supported and built up by Aurich et al, 37 who could show the functional integration of hepatocytes derived from BM MSCs into mouse livers. For this purpose the MSCs were preconditioned in vitro resulting in storage of glycogen, synthesis of urea and activation of hepatocyte-specific gene promoter of phosphoenolypyruvate carboxykinase (PCK1).…”
Section: Differentiation Of Bm-derived Mscs Towards Liver Progenitor supporting
confidence: 75%
“…In animal models, the most promising cells for therapy appear to be mesenchymal stem cells (MSCs). If human MSCs are xenografted to the allyl alcohol-damaged livers of immunosuppressed rats, large groups of human albumin-positive hepatocytes are generated without cell fusion being involved [105]. Transplanted human MSCs also contribute to the hepatocyte mass, predominantly periportally, in the partially hepatectomized livers of immunodeficient mice when regeneration is impeded by a β-receptor antagonist [106].…”
Section: Bone Marrowmentioning
confidence: 99%